Epithelial Ovarian Cancer: Rationale for Changing the One-Fits-All Standard Treatment Regimen to Subtype-Specific Treatment. Issue 3 (1st March 2014) - Despierre, Evelyn; Yesilyurt, Betül T.; Lambrechts, Sandrina; Johnson, Nick; Verheijen, René; van der Burg, Maria; Casado, Antonio; Rustin, Gordon; Berns, Els; Leunen, Karin; Amant, Frédéric; Moerman, Philippe; et al.
Abstract : Objective: Epithelial ovarian cancers (EOCs) are, although still treated as a single disease entity, often classified into type I tumors (low-grade serous, mucinous, endometrioid, clear cell) and type II tumors (high-grade serous, undifferentiated cancers, carcinosarcomas). The aim of our study was to determine the incidence, clinical relevance, and prognostic and predictive impact of somatic mutations in both types I and II EOCs. Methods: Two hundred sixty-two evaluable, primary, high-risk stage I (grade 3, or aneuploid grade 1 or 2, or clear cell) and stage II-IV EOCs, collected at the University Hospitals Leuven and within the European Organisation for Research and Treatment of Cancer 55971 trial, were genotyped for hotspot mutations in KRAS (COSMIC [Catalogue of Somatic Mutations in Cancer] coverage >97%), BRAF (>94%), NRAS (>97%), PIK3CA (>79%), PTEN, FBXW7 (>57%), AKT2, AKT3, and FOXL2, using Sequenom MassARRAY. Results: Of the 13% histopathologically classified type I tumors, 49% were KRAS or PIK3CA mutant versus only 2.9% in the type II tumors (87%). Mucinous subtypes harbored significantly more KRAS mutations than all nonmucinous tumors (50% vs 4%, P < 0.001). PIK3CA mutations were predominantly found in clear cell carcinomas (46.2%) and endometrioid carcinoma (20%) and were frequently associated with endometriosis. Moreover, low-grade serous tumors were more frequently KRAS or BRAF mutated (44%) than high-grade serous tumors (0.6%). KRAS or PIK3CA mutation did not correlate with progression-free survival or overall survival. Mutations in NRAS, PTEN, FBXW7, AKT2, AKT3, and FOXL2 were rare (<1%). Conclusions: Somatic mutations are rare in type II EOCs, whereas type I EOCs contain distinct diseases with different driver mutations. In general, these tumors respond worse to standard paclitaxel carboplatin therapy. Clinical trials with molecular targeted therapy in the different subtypes of type I tumors are urgently needed using this theragnostic information.